Dynamic bipedal locomotion based on hybrid zero dynamics control. - Oliveira, Arthur Castello Branco de (2019)
This work presents an alternative method for 3D bipedal gait design using independent controllers for the plane of motion frontal and sagittal. The use of virtual constraints to design a stable gait for the frontal system is fully developed and studied in this work and the resulting gait simulated. The results, although not definitive, are promising.